PENGARUH RISIKO SUKU BUNGA THE FED, RISIKO INFLASI, DAN RISIKO KURS RUPIAH TERHADAP IHSG - Monica, Aurenshia; Fitanto, Bahtiar (Contemporary Studies in Economic, Finance and Banking, 2024)
There are external (macro) factors such as monetary and fiscal policies that companies can’t control. The rise in interest rates, the depreciation of exchange rates, and the inflation would cause high fluctuations in capital markets. This research aims to analyze the impact of interest rates, Rupiah exchange rate risk against the Dollar, and inflation rates on Composite Index. The approach used is a quantitative approach with the Error Correction Model (ECM) analysis method during the period 2017 – 2022. Independent variables include The Fed's interest rate risk, inflation risk, and Rupiah exchange rate risk, while the dependent variable is stock prices. The research results show that the risk of the Fed interest rate and the risk of the Rupiah exchange rate against the Dollar had a negative and significant effect, while inflation risk had no significant effect on the Composite Index.  This research is expected to provide benefits for investors, policy makers, stock regulators, and readers to see the analysis of changes in stock prices due to changes in macroeconomic variables.